Gynecological aftercare after cancer in children and adolescents Gynäkologische Nachsorge nach onkologischer Erkrankung im Kindesund Jugendalter - Lubrich, Hannah; Oppelt, Patricia (Internistische Praxis, 2023)
Cancer in children and adolescents can now be treated successfully due to a wide variety of different treatments. However, the side effects of these treatments often emerge years after the oncological disease. Hormonal (long-term) effects, thyroid and hypothalamic-pituitary-axis irregularities and impaired growth or development in puberty are particularly common examples. A delayed or premature onset of puberty can also occur. A long-term aftercare with an endocrinologist is imperative in order to detect any irregularities in children and adolescents. It is therefore important to regularly examine patients, paying particular attention to height, weight and the tanner-scale. Treatments such as chemo- and radiotherapy can potentially lead to infertility, which can severely impact a patient‘s quality of life. Treatments are tailored to shield the female reproductive organs, however, should this not be possible, fertility-conserving methods must be discussed with young female patients. Methods include ovariopexy for a planned radiotherapy, the introduction of a GnRH modulator for a planned chemotherapy and the extraction and cryoconservation of egg cells or ovarian tissue depending on the patient’s age. The cryoconservation of ovarian tissue is most likely the only option in prepubescent girls.
CRIS-Team Scopus Importer:2023-10-20
Keywords: adolescents; cancer; children; gynaecological aftercare